Case Report: Molecular characterization of rabies virus transmitted from a dog to a bull in a livestock market in Ghana - Odoom, Theophilus; Abbiw, Richard Kwamena; Abuh, Joseph Kofi; Allegye-Cudjoe, Emmanuel; Johnson, Sherry Ama Mawuko; Tasiame, William; Arthur, Daniel; Anderson, Benita; Settypalli, Tirumala B. K.; Lamien, Charles E.; Dundon, William G. (Frontiers in Veterinary Science, 2025)
On the 24/09/2023, a video of a suspected rabid bull at a livestock market in Ghana was shared on social media and was seen by a local veterinary officer. This led to an on-site investigation by veterinary authorities on the 25/09/2023 which concluded that the bull had been bitten by a three-month old dog 4 days previously. The puppy, which was killed and buried after the bite, was subsequently exhumed, tested and confirmed positive for rabies. The bull was humanely destroyed. Brain tissue from the bull was collected and sent to the Accra Veterinary Laboratory for further analysis. RABV was confirmed by conventional RT-PCR and the full genome of the viruses from both animals were sequenced. The consensus sequences of the genomes belonging to the Africa 2 clade, were identical although sub-consensus variants in a subset of the sequences located in the RNA-dependent-RNA polymerase (L) gene of the bovine virus were observed. The implication of these findings is discussed.